A Novel Interprofessional Mock Clinic Workshop for Medical Students With Orthotics and Prosthetics Students - Sanghamitra M. Misra; Josh B. Utay; Larry Laufman (Association of American Medical Colleges, 2019)
Introduction Medical school education on orthotics and prosthetics (O&P) is limited, and O&P students receive limited education on performing comprehensive histories and physicals (H&Ps). This interprofessional workshop brings medical and O&P students together in a mock clinical setting. Students from one profession appraise the relationship of their scope/role to those of students of the other profession. Methods Third-year medical students, second-year O&P students, and O&P patients participated in a 3-hour workshop. Students partnered into groups and rotated among stations performing patient history, physical exam, and O&P assessment. As a medical or O&P student completed the H&P, she or he explained the process to the student of the other profession. Each group assessed two patients and then presented one to a physical medicine and rehabilitation (PM&R) attending physician. The workshop concluded with a feedback session. Results Immediate feedback was positive. Medical students, O&P students, PM&R physicians, and patients all commented favorably. In the workshop's first year, there were 19 responding students (10 medical, nine O&P); 68.4% said that the clinical session was better than expected, 73.7% were satisfied with the overall event, and 73.7% felt they were likely to use what they had learned in clinical practice. Feedback from learners included requesting more time for students to interact with each other after the mock clinic, sending preparation materials before the session, and focusing the medical student H&P on the musculoskeletal exam. Discussion This workshop was well received by participants. Their feedback will help to continue and expand this collaboration.